Experimental study on fracture properties of dam concrete under post‐peak cyclic loading based on DIC and acoustic emission techniques. Issue 9 (1st July 2022) - Bu, Jingwu; Xu, Huiying; Wu, Xinyu; Chen, Xudong; Xu, Bo
Abstract: In order to study the fracture properties of dam concrete under post‐peak cyclic loading, wedge splitting tests with three loading rates were performed on notched cubic specimens. Meanwhile, the acoustic emission (AE) and digital image correlation (DIC) technologies were used to monitor crack propagation in the specimens. As the loading rate increases, the peak load increases, and stiffness degradation increases. The cumulative AE counts show a step increasing trend and exhibit a Kaiser effect, which decreases via the post‐peak cyclic loading procedure and increases as the loading rate increases. The AE energy fluctuates markedly, and b value fluctuates frequently with an increasing loading rate. As the loading rate increases, the strain recovery rate decreases, and the permanent crack increases. The effective crack length gradually and steadily increases, and as the loading rate increases, the growth rate of the effective crack length increases.